2010
DOI: 10.1007/s11999-009-0933-4
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rate after Spine Surgery in Cerebral Palsy is High and Impairs Results: Multicenter Analysis of Risk Factors and Treatment

Abstract: Infection is a serious complication of surgery to correct scoliosis in patients with cerebral palsy (CP). We obtained multicenter representative figures for deep and superficial infection rates, analyzed risk factors and treatment outcomes, and compared deformity correction relative to infection. We retrospectively reviewed 157 patients who had posterior spinal fusion for CP at one of eight centers. Preoperative and intraoperative variables were subjected to multivariate analysis to determine factors predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 11 publications
5
43
2
1
Order By: Relevance
“…Our studies also observed that prolonged preoperative hospitalization, extended surgery duration, high blood loss [53,54], cognitive impairment, severity of deformity, use of allograft [11,51,55], urinary tract infection and [54,56] and malnutrition [57][58][59] are some of the complexities affiliated with surgical treatment of NMS patients and are also proven risk factors for infections. Szoke et al [36] elaborate that the infected cases in their series had spastic quadriplegia with severe mental retardation, seizures and speech inability; these patients had also received allogenic transfusion subsequent to high blood loss.…”
Section: Infectionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our studies also observed that prolonged preoperative hospitalization, extended surgery duration, high blood loss [53,54], cognitive impairment, severity of deformity, use of allograft [11,51,55], urinary tract infection and [54,56] and malnutrition [57][58][59] are some of the complexities affiliated with surgical treatment of NMS patients and are also proven risk factors for infections. Szoke et al [36] elaborate that the infected cases in their series had spastic quadriplegia with severe mental retardation, seizures and speech inability; these patients had also received allogenic transfusion subsequent to high blood loss.…”
Section: Infectionmentioning
confidence: 53%
“…Our sensitivity analysis suggests that a larger cohort exhibits lower implant complication rates (6.5 %). Sponseller et al [56], whose main objective was to study infection rates after surgery, mention two cases of implant removal due to infection. Since their main objective was to report infections, other non-infection related implant complications, even if present, were not likely to be mentioned.…”
Section: Implant-related Complicationsmentioning
confidence: 99%
“…2 In certain specific populations, such as patients with multiple injuries or neuromuscular disease, this can rise to 10%. 3,4 Due to its relatively low incidence, the consequences of SSI and its potential influence on patient outcome are still poorly defined, which limits the amount of useful advice that can be given to patients pre-operatively.…”
mentioning
confidence: 99%
“…Similar rates were reported in other studies. 5,6,8 In a recent multicenter review, Sponseller et al 62 identified significant wound infection rates of 6% deep and 4% superficial. The use of unit rods was associated with significantly higher rates of infection than custom bent rods, although a clear reason for this finding was unknown.…”
Section: Postoperative Complicationsmentioning
confidence: 99%